Rank-Order Tournaments, Probability of Winning and Investing in Talent: Evidence from Champions League Qualifying Rules - Colin P. Green; Fernando A. Lozano; Rob Simmons (Institute for the Study of Labor (IZA), 2015)
We analyse how a change in the probability of winning a tournament affects an agent's effort using the qualification rules for entry into the group and playoff stages of the UEFA Champions' League. Our results suggest that increasing the number of slots that a national league gets in the Champions' League leads to increases in investment in talent ex ante. This effect is largest among the teams that in the previous season just failed to qualify. This suggests that changes in prize structure leads to changes in investment decisions amongst those clubs most affected at the margin. However, we also find that incumbent teams that have already qualified for the Champions' League simultaneously raise their efforts, consistent with the occurrence of an arms race among top European football teams.
Keywords: M5; 330; tournaments; UEFA Champions League